IMPLEMENTASI KEBIJAKAN TRANSPORTASI PUBLIK OLEH DINAS PERHUBUNGAN PROVINSI RIAU DALAM MENJAMIN KESELAMATAN PENUMPANG ANGKUTAN UMUM ANTAR KOTA DALAM PROVINSI - Winda Oktavia; Rizky Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of passenger safety in the implementation of public transportation, particularly intercity public transportation within provinces (AKDP) in Riau Province. The high rate of traffic accidents and the limited availability of supporting safety facilities indicate that the implementation of transportation policies has not been optimal. This study aims to analyze the implementation of public transportation policies by the Riau Provincial Transportation Agency in ensuring passenger safety, as well as to identify the obstacles faced in their implementation. This research uses a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation involving informants from the Transportation Agency, drivers, and passengers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The study applies Edward III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The results show that the implementation of public transportation policies in ensuring passenger safety in AKDP in Riau Province has not been optimal. This is due to ineffective policy communication, limited resources, insufficient commitment from implementers, and less efficient bureaucratic structures. In addition, there are still unfit vehicles operating and inadequate safety facilities.